INTEGRATION OF RELIGIOUS ATTITUDES AND CRITICAL THINKING SKILLS IN ISLAMIC EDUCATION AT THE PEMBANGUNAN UIN JAKARTA MADRASAH ALIYAH - Siregar, Nova sari; Mukti, Abdul; Khalimi, Khalimi (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the integration of religious attitudes and critical thinking skills in Islamic Religious Education (PAI) learning at Madrasah Aliyah Pembangunan UIN Jakarta. The research focuses on the condition of students’ religious attitudes and critical thinking skills, the forms of integration within the learning process, the strategies used by PAI teachers in implementing the integration, as well as the supporting and inhibiting factors encountered. The research method employed is qualitative with a case study design. The data sources consist of PAI teachers, students, the vice principal for curriculum affairs, and supporting documents such as lesson plans, syllabi, teaching modules, and learning records. Data were collected through classroom observation, in- depth interviews, and documentation. Data validity was tested through triangulation of sources, techniques, and time. Data analysis used the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the integration of religious attitudes and critical thinking is reflected in PAI learning processes centered on dialogue, reflection, and active student engagement. Teachers act as facilitators who connect Islamic values with higher-order thinking skills through problem-based learning, reflective discussions, and project-based learning strategies. Supporting factors include teacher competence, curriculum support, and the religious culture of the madrasah, while inhibiting factors include limited instructional time, students’ tendency toward passive learning, and the lack of teacher training in critical pedagogy.The study concludes that the integration of religious attitudes and critical thinking skills in PAI learning can enhance the quality of learning, making it more meaningful, holistic, and contextual. The practical implication is the need to strengthen innovative teaching strategies that combine values and critical reasoning within the PAI curriculum.